Application of remote sensing in the investigation of maturity age of palm oil trees In Pasir Puteh, Kelantan / Faradina Marzukhi and Siti Noor Safiyyah Sauti - Marzukhi, Faradina; Sauti, Siti Noor Safiyyah (Universiti Teknologi MARA, Perlis, 2018)
The determination of oil palm age is essential for the plantation industry as it influences the growth and yield production of the plantation. The aim of this study is to identify the maturity age of oil palm trees using remote sensing technique. Satellite image, SPOT 7 with 6 meter resolution is used in this research study. Ground data is collected to know the height, age and production of the oil palm plantation. Satellite image data is obtained from Malaysian Remote sensing Agency (MRSA) while the ground data is acquired from Malaysian Palm Oil Board (MPOB). The processing is carried out via Erdas Imagine and ArcGIS software. The pixel value for three different ages of oil palm trees, 1 year, 2 year and 5 year are observed to analyze the pixel value for different tree ages. Then, the spectral reflectance of the trees are observed for each of the age. Vegetation indices of NDVI and SAVI are carried out to observe the health of the plantation. Next, the regression model between age and palm oil growth is modeled. The regression shows the relationship of the age and growth. The final result is the map showing the healthy level of oil palm trees using Normalized Difference Vegetation Index (NDVI) and Soil Adjusted Vegetation Index (SAVI).